Evidence of populational Burkholderia pseudomallei exposure in Madagascar - Razafimahatratra, Solohery Lalaina; Avotra Andrianambinintsoa, Sarobidy Tsiory; Rasoloharimanana, Lova Tsikiniaina; Rajerison, Minoarisoa; Rasolofo, Voahangy; Hall, Carina M.; Celona, Kimberly R.; Yi, Jinhee; Keim, Paul; Wagner, David M.; Settles, Erik W.; Schoenhals, Matthieu (PLOS Neglected Tropical Diseases, 2025)
Author summary Melioidosis is a serious and potentially fatal infectious disease caused by the environmental bacterium Burkholderia pseudomallei (Bp), which is naturally found in soil and surface water. The disease primarily affects individuals with underlying conditions such as diabetes and can lead to severe illness or death if not promptly diagnosed and treated. Despite its clinical severity, melioidosis often goes undiagnosed in low-resource settings due to the need for specialized laboratory diagnostics. In Madagascar, only a handful of human cases have been officially reported, but the true extent of exposure across the population has remained unknown. To address this gap, we conducted a large-scale serological survey, analyzing blood samples from more than 5,000 healthy blood donors across five regions of the country. By screening for antibodies indicative of past infection, we uncovered a significantly higher seroprevalence in the coastal region of Mahajanga, pointing to localized transmission. Supporting these findings, we also detected B. pseudomallei DNA in surface water samples from the same region, providing environmental evidence of exposure risk. These results suggest that melioidosis may be more widespread in Madagascar than previously recognized. Our study underscores the importance of strengthening disease surveillance and environmental monitoring while raising awareness of this neglected tropical disease. It also highlights the potential of using blood donor samples as a cost-effective and scalable tool for uncovering hidden infectious threats in resource-limited settings.